Brucella abortus interferes with the inflammatory response and tissue repair in mice - M. F. Silva; D. F. A. Batista; C. Eckstein; F. B. Costa; P. P. Campos; M. A. N. D. Ferreira; M. S. S. Araújo; O. A. Martins-Filho; R. M. Tsolis; R. L. Santos; Tatiane A. Paixão (Scientific Reports)
Abstract Brucellosis caused by Brucella spp. is considered a debilitating chronic zoonotic disease. B. abortus, which is endemic in many countries, is responsible for chronic bovine and human infections. Interestingly, there are joint and breast implant infections caused by Brucella spp. Although Brucella spp. induce an insidious inflammatory response, little is known about the influence of bacteria on the establishment of early inflammation in vivo, particularly in a synthetic sponge model. B. abortus 2308 was able to survive and replicate in this model, whereas B. abortus Δ virB2 was attenuated, confirming its inability to cause persistent infection. Compared with Δ virB2, B. abortus 2308 is able to modulate the inflammatory response in sponge. We observed that B. abortus 2308 induced a lower influx of inflammatory cells and inflammatory mediators and the formation of fibrovascular tissue at 14 days postimplantation than the control or ΔvirB2-infected mice. Compared with the uninfected sponge, infection by B. abortus in the sponge prolonged the percentage of Mф and M1 macrophages, in addition to increasing the percentage of CD8 + T lymphocytes. B. abortus 2308 can inhibit inflammation in vivo, and the T4SS influences the course of the acute inflammatory process in a synthetic matrix model.